2020
DOI: 10.1016/j.ijid.2020.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Lassa Fever Induced Hearing Loss: The Neglected Disability of Hemorrhagic Fever

Abstract: Lassa fever (LF), a hemorrhagic fever endemic to West Africa, has an incidence of approximately 500,000 cases per year. This study evaluated hearing loss and other sequelae following LF. Methods: This case-control study enrolled laboratory-confirmed LF survivors, non-LF febrile controls and matched-community controls with no history of LF or recent hospitalization for a febrile illness. Study participants completed a symptom questionnaire. Pure-tone audiometry was completed by a subset of participants. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The more common viral etiologies include CMV, rubella, mumps, and tropical pathogens such as chikungunya, Zika, and Lassa fever viruses [ 16 , 33 , 42 49 ]. Although previous studies have suggested that direct viral damage to structures of the inner ear such as the stria vascularis, cochlea, and neuronal damage may be responsible in mumps and rubella, a host immune response to viral antigens in CMV, or the development of a vasculitis or autoimmune disease as in Lassa fever have been hypothesized [ 16 , 45 ]. However, definitive evidence of any mechanism of pathogenesis is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The more common viral etiologies include CMV, rubella, mumps, and tropical pathogens such as chikungunya, Zika, and Lassa fever viruses [ 16 , 33 , 42 49 ]. Although previous studies have suggested that direct viral damage to structures of the inner ear such as the stria vascularis, cochlea, and neuronal damage may be responsible in mumps and rubella, a host immune response to viral antigens in CMV, or the development of a vasculitis or autoimmune disease as in Lassa fever have been hypothesized [ 16 , 45 ]. However, definitive evidence of any mechanism of pathogenesis is limited.…”
Section: Discussionmentioning
confidence: 99%
“…There were both unilateral and bilateral cases of hearing loss. Ficenec et al [15] reported 30% cases of bilateral hearing loss, while Cummins et al [13] reported 50% cases of bilateral hearing loss.…”
Section: Hearing Loss Among Lassa Fever Patientsmentioning
confidence: 99%
“…Mertens et al reported an incidence of 30% in Liberia [11]. Ibekwe reported an incidence of 13.5% in Nigeria [14] and Ficenec et al reported an incidence of 17% in Sierra Leone [15]. All these countries are in Lassa fever endemic region in West Africa.…”
Section: Open Journal Of Preventive Medicinementioning
confidence: 99%
“…Four of the 22 imported Lassa fever cases (18.2%) had hearing loss. Hearing loss is a common finding among Lassa fever patients in the endemic region, especially when assessed by pure tone audiometry rather than by self-reported hearing loss [43]. Because Lassa fever related hearing loss is not among the early symptoms of Lassa fever, it may not be a very helpful diagnostic symptom if an early diagnosis of Lassa fever is desired.…”
Section: Findings Of Clinical Features Of Lassa Fever Cases Inmentioning
confidence: 99%